Melanocortin 4 receptor activates ERK-cFos pathway to increase brain-derived neurotrophic factor expression in rat astrocytes and hypothalamus. (15th August 2015) - Ramírez, D.; Saba, J.; Carniglia, L.; Durand, D.; Lasaga, M.; Caruso, C.
Highlights: MC4R mechanisms of action were studied. MC4R-induced BDNF expression involves ERK and cFos activation in astrocytes and rat hypothalamus. Inhibition of PI3K, Src and RSK blocked MC4R-induced BDNF expression in astrocytes. Graphical Abstract: Abstract: Melanocortins are neuropeptides with well recognized anti-inflammatory and anti-apoptotic effects in the brain. Of the five melanocortin receptors (MCR), MC4R is abundantly expressed in the brain and is the only MCR present in astrocytes. We have previously shown that MC4R activation by the α-melanocyte stimulating hormone (α-MSH) analog, NDP-MSH, increased brain-derived neurotrophic factor (BDNF) expression through the classic cAMP–Protein kinase A–cAMP responsive element binding protein pathway in rat astrocytes. Now, we examined the participation of the mitogen activated protein kinases pathway in MC4R signaling. Rat cultured astrocytes treated with NDP-MSH 1 µM for 1 h showed increased BDNF expression. Inhibition of extracellular signal-regulated kinase (ERK) and ribosomal p90 S6 kinase (RSK), an ERK substrate, but not of p38 or JNK, prevented the increase in BDNF expression induced by NDP-MSH. Activation of MC4R increased cFos expression, a target of both ERK and RSK. ERK activation by MC4R involves cAMP, phosphoinositide-3 kinase (PI3K) and the non receptor tyrosine kinase, Src. Both PI3K and Src inhibition abolished NDP-MSH-induced BDNF expression. Moreover, we found that intraperitoneal injection of α-MSH induces BDNF and MC4R expression and activates ERK and cFos in male rat hypothalamus. Our results show for the first time that MC4R-induced BDNF expression in astrocytes involves ERK-RSK-cFos pathway which is dependent on PI3K and Src, and that melanocortins induce BDNF expression and ERK-cFos activation in rat hypothalamus.